Goya and Alberti facing bullfighting: a study of inter-artistic and structural confluences in Suerte de matar and El matador (El Hilo de la Fabula, 2025)
This research analyses the representational convergences of the bullfighting act in Francisco de Goya's painting Suerte de matar and Rafael Alberti's poem El matador, relating the two works on the basis of their structural and thematic similarities in the depiction of the climax of the bullfight. The study of inter-artistic categories, including the depiction of folklore and bullfighting, is employed to analyse the compositional and structural elements that imbue the scene with dynamism. These elements encompass the visual and formal arrangement in the pictorial work, as well as the rhetorical organisation of the poetic text. Despite the absence of direct influences between the authors, there are notable parallels in the choice of the representative approach to the pregnant moment, which allows us to trace a line of ideological continuity between the two artistic manifestations.
Keywords: inter-artistic analysis; inter-artistic comparison; scenic poem; Francisco de Goya; Rafael Alberti